Pengaruh E-Wom dan Brand Awareness terhadap Purchase Intention di Restoran Nippon-Kan Jakarta Pusat - Chika Yacinta Rahardjo; Natalia Paserela; Juliana Juliana (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Apart from providing rooms, the hotel also provides a restaurant. One of the restaurants in Central Jakarta is the Japanese restaurant Nippon-Kan. Entering the digital era, internet-based marketing has begun to be utilized by business actors. E-WOM is a marketing strategy that is widely used today. By utilizing the internet, customer information and reviews about restaurants will be widely disseminated in various discussion forums so that E-WOM can influence customer purchase intentions. In addition to E-WOM, brand awareness can also affect customer purchase intentions. This study aims to inspect and evaluate the effect of E-WOM and brand awareness on purchase intentions at Nippon-Kan restaurants. The theories used are marketing theory, brand theory, and planned behavior theory. The research method used was to collect data through a questionnaire and then process it with SmartPLS 3.2.9. The results of the study explain that E-WOM and brand awareness have a positive and significant outcome on purchase intentions at the Japanese restaurant Nippon-Kan, Central Jakarta. The implication of this research is that it can be deliberation for every company to increase E-WOM and brand awareness that has been implemented. For the public, this research is expected to afford information and knowledge about E-WOM, brand awareness and consumer purchase intentions. For academics, this research is expected to give new and additional references for further research.Keyword: Brand Awareness; E-WOM; Purchase Intention